2016
DOI: 10.1007/s11357-016-9923-0
|View full text |Cite
|
Sign up to set email alerts
|

Telomere attrition in beta and alpha cells with age

Abstract: We have reported telomere attrition in β and α cells of the pancreas in elderly patients with type 2 diabetes, but it has not been explored how the telomere lengths of these islet cells change according to age in normal subjects. To examine the telomere lengths of β and α cells in individuals without diabetes across a wide range of ages, we conducted measurement of the telomere lengths of human pancreatic β and α cells obtained from 104 autopsied subjects without diabetes ranging in age from 0 to 100 years. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…As a result of insulin resistance, pancreatic ␤-cell hyperplasia has been observed, which can lead to proliferative exhaustion and senescence of ␤-cells (140,177). Furthermore, the number of pancreatic ␤-cells decreases with age because of a decline in turnover in elderly people (179). Besides a lower number of ␤-cells, senescence of ␤-cells can also lead to a decrease in insulin production in T2DM (180).…”
Section: Pancreatic Cellular Senescencementioning
confidence: 99%
“…As a result of insulin resistance, pancreatic ␤-cell hyperplasia has been observed, which can lead to proliferative exhaustion and senescence of ␤-cells (140,177). Furthermore, the number of pancreatic ␤-cells decreases with age because of a decline in turnover in elderly people (179). Besides a lower number of ␤-cells, senescence of ␤-cells can also lead to a decrease in insulin production in T2DM (180).…”
Section: Pancreatic Cellular Senescencementioning
confidence: 99%
“… 5 , 21 , 22 , 23 , 24 Our previous study demonstrated that age is an independent risk factor for NODM in patients with idiopathic membranous nephropathy treated with ISDs. 6 Glucose tolerance progressively declines with age, 25 which may be caused by the shortening of telomeres in β and α cells 26 and by age‐related changes in DNA methylation in human islet cells. 27 These two effects may explain the main study finding that older age increased the risk of developing NODM.…”
Section: Resultsmentioning
confidence: 99%
“…Studies examining the association between α cell mass and age in humans report no drastic changes in α cell mass across time (Henquin & Rahier 2011, Moin et al 2020. However, aged human islet endocrine cells display higher rates of transcriptional noise, increased expression of stress response genes, and shortened telomeres, suggesting that age may influence cell identity and/or function (Tamura et al 2016, Enge et al 2017. Studies of non-human primate α cells support this, where downregulated genes in aged α cells were enriched for gene ontology terms associated with peptide secretion and multiple metabolic processes (Li et al 2020).…”
Section: Agingmentioning
confidence: 99%